Implementation of Religious Development Programmed in Improving Students' Religious Attitude: Study at SMPN 27 Bandung - Thena Sutinah Thena; Miftahul Huda; Iim Ibrohim; Mukhlishah Mukhlishah; Supala Supala (Institut Agama Islam Persis Bandung, 2024)
School is a place where students pursue knowledge. Every school generally has a vision and mission related to religious values, aiming to produce a generation with strong religious character. However, based on recent observations, there are still students who display behaviors that indicate a lack of religious attitude, such as speaking harshly, being undisciplined, and lacking manners. This phenomenon underlies the importance of this study, which investigates the implementation of religious development programs at SMPN 27 Bandung in fostering religiosity among students as part of the Islamic generation. This research aims to explore the religious development programs, their implementation, the supporting (internal and external) and inhibiting (internal and external) factors, as well as the impacts of these programs. The study uses a descriptive-analytical method with a qualitative approach. Data were collected through observation, interviews, and documentation review, analyzed using triangulation techniques. The findings reveal that the implementation of the religious development program has a positive impact on enhancing students' religious attitudes. This is evidenced by the improvement in: (1) humility, (2) respect for religious diversity (tolerance), and (3) cooperation in preparing prayer spaces